Synchronous angiomyolipoma with epithelial cysts and clear cell renal cell carcinoma: a case report - Wang, Jian; Ren, Chengde; Qiang, Ziyang; Li, Jintao; Ren, Hailin; Chen, Guojun; Gong, Xue; Zhang, Jiaxin (Frontiers in Oncology, 2025)
BackgroundAngiomyolipoma with Epithelial Cysts (AMLEC) is a rare renal tumor that has been established as a separate pathological entity in recent years. Existing literature has focused on its histological origin, molecular features, and imaging characteristics. To our knowledge, this is the first reported case of AMLEC coexisting with clear cell renal cell carcinoma (ccRCC).Case presentationA 37-year-old male presented with lumbar pain and persistent gross hematuria. Imaging revealed tumor rupture with hemorrhage, initially suggestive of cystic renal cell carcinoma. However, postoperative pathology and immunohistochemistry confirmed a diagnosis of AMLEC combined with ccRCC.ConclusionAMLEC is a rare subtype of angiomyolipoma (AML) that typically lacks adipose tissue, with an epithelial component likely derived from dilated renal tubules. Its unique histological features and immunohistochemical staining are key to pathological diagnosis. This report also reviews prior cases of AMLEC and synchronous renal tumors, offering a valuable reference for clinical diagnosis and management.